Dreams of a Solo Traveller: Exploring Cultural Identity and Gender Roles Through Silk and Poetic Visual Communication - Li, Qiainyin; Mortensen Steagall, Marcos (Translator) (School of Art and Design, AUT, 2024)
Dreams of a Solo Traveller offers a reimagined perspective on the Chinese term 剩女 (Shèngnǚ or "Leftover Woman"), a label often applied to unmarried, urban professional women over the age of 27. In this research, the term is reframed to represent women who, rather than adhering to traditional marital expectations, deliberately pursue alternative paths for their future. The study is informed by personal experiences as well as literature on the familial and societal pressures faced by many young Chinese women today. A central concept in the research is the discursive interplay between poetry and painting, encapsulated in the Chinese expression 诗中有画/画中有诗 (‘painting in poetry and poetry in painting’). 诗中有画 refers to the vivid imagery found in poetry, while 画中有诗 reflects the poetic essence within painting. This ancient Chinese practice of blending literary and visual art forms is a key influence on the study, which uses this relationship to express contemporary social issues through design. The project explores how poetry, calligraphy, fabric design, illustration, and printing—utilized on silk—can challenge and reimagine societal gender expectations. Seven original poems, presented on draped silk, bring a modern interpretation to the concept of ‘painting in poetry and poetry in painting,’ applied in a visual communication design context. Each work is accompanied by a catalogue that includes English translations of the poems and concise explanations of each piece.